Pengaruh Pengeluaran Pemerintah pada Sektor Kesehatan, Pendidikan, Infrastruktur dan Tingkat Kemiskinan terhadap Indeks Pembangunan Manusia di Kabupaten/Kota di Tiga Provinsi Termiskin di Pulau Sumatera - Afrilia Ulfatussaniah; Asih Murwiati; Heru Wahyudi (Departement of Mathematics Education, 2024)
This study aims to see the effect of government on the health sector, education, infrastructure and poverty levels on the human development index.This study uses 4 independent variables, namely: Percentage of poverty, allocation of regional expenditure in the education sector, allocation of regional expenditure in the health sector and allocation of regional expenditure in the infrastructure sector (housing and public facilities) and for the dependent variable in this study is the Human Development Index. The scope of this study includes 50 districts / cities in the three poorest provinces on the island of Sumatra, namely Aceh, Bengkulu and South Sumatra provinces using a 5-year time span, namely 2017 - 2021. The results of this study indicate that government expenditure on the health and education sectors has a positive effect while the infrastructure and poverty sectors have a negative effect on the human development index.